Peningkatan Kesadaran Masyarakat terhadap Resiko Judi Online dan Pinjaman Online melalui Sosialisasi Manajemen Keuangan di Majlis Taklim Nurul Iman - Utami, Tri; Aprilia, Erika Astriani; Irawati, Wiwit (Abdimisi, 2025)
This Community Service Program (PKM) was conducted in collaboration with Majlis Ta’lim Nurul Iman, located in Serua Sub-district, Bojongsari District, Depok City, West Java Province. The main objective of this PKM activity was to provide financial management education to the women members of Majlis Ta’lim Nurul Iman and to introduce them to the concept of financial technology, particularly Peer-to-Peer (P2P) Lending or online loans, as well as to raise awareness about the dangers of online gambling. The target participants were approximately 30 housewives who are members of the Majlis Ta’lim, with the activity taking place on May 4, 2025. The methods used in this PKM included lectures, tutorials, discussions, and mentoring. The results showed that most participants were familiar with online loan and gambling applications, but lacked an understanding of the risks associated with choosing the wrong loan services. After the session, participants gained insights and tips to avoid falling into the traps of illegal online loans and gambling. Keywords: Fintech, Online Gambling, Online Loans, P2P Lending, Financial Literacy, Financial Management